1991
DOI: 10.1007/bf03392860
|View full text |Cite
|
Sign up to set email alerts
|

A standard methodology for the analysis, recording, and control of verbal behavior

Abstract: Lack of a standard methodology has been one of the major obstacles preventing advancement of behavior analytic research in verbal behavior. This article presents a standard method for the analysis, recording, and control of verbal behavior that overcomes several major methodological problems that have hindered operant research in verbal behavior. The system divides all verbal behavior into four functional response classes, correct, error, no response, and inappropriate behavior, from which all vocal responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…Alguns autores da Análise do Comportamento (Donahoe, 1998;Drash & Tudor, 1991;Leigland, 1998) têm afirmado que a proposta de Skinner (1957de Skinner ( /1992 para o estudo do comportamento verbal não gerou um campo de pesquisa expressivo. Os resultados do presente trabalho, porém, apontam que o estudo do comportamento verbal no Brasil, de acordo com a proposta conceitual de Skinner, estabeleceu-se como programa de pesquisa (i.e.…”
Section: Considerações Finaisunclassified
“…Alguns autores da Análise do Comportamento (Donahoe, 1998;Drash & Tudor, 1991;Leigland, 1998) têm afirmado que a proposta de Skinner (1957de Skinner ( /1992 para o estudo do comportamento verbal não gerou um campo de pesquisa expressivo. Os resultados do presente trabalho, porém, apontam que o estudo do comportamento verbal no Brasil, de acordo com a proposta conceitual de Skinner, estabeleceu-se como programa de pesquisa (i.e.…”
Section: Considerações Finaisunclassified
“…The verbal behavior program used with these infants and their parents was essentially the same as that used to successfully increase the verbal behavior and cognitive skills oftypical infants ranging in age initially from 3 to 6 months (Drash & Tudor, 1990;Storfer, 1990). Thus, within the behavior analysis community we already have the technology necessary to proceed with programs of prevention and earlier intervention in autism (Bijou, 1983;Drash, High, & Tudor, 1999;Drash & Tudor, 1991). As Malott (2004) stated, "We do not want to be a western version ofthe Pacific-island cargo cults waiting generation after generation, for the ship laden with the gene-fixing, autism-curing pills that will so easily take care of all of our problems."…”
Section: A Theoretical Analysis Of Etiological Factors In Autismmentioning
confidence: 99%
“…Results indicated that the bizarre verbal behavior emitted by an adult with schizophrenia occurred almost exclusively during the attention condition, indicating that the behavior was maintained by social positive reinforcement. Drash and Tudor (1991) call for a standard methodology to analyze contingencies that support verbal behavior. The present study extends the body of behavior-analytic research using functional analysis as a tool to analyze verbal behavior.…”
mentioning
confidence: 99%